Hubungan antara Asthma Control Test (ACT) dengan spirometri sebagai alat pengukur tingkat kontrol asma - Efzah Efzah; Zuhrial Zubir (Fakultas Kedokteran USU, 2017)
Introduction :Asthma is a chronic respiratory disease that still a serious health problem worldwide. IIis nown that there is no cure for asthma, but tile disease can be c:ontrolled in some pati1:m.k;l111rn:1 t;u11lrulis fucuses on the adequacy therapy. GINA guideline for theassessment of asthma control using gauges lung ruriction, but this evaluation is difficult because of lack of facilities spir:imetry as a measure of lung function in primary care.Asthma control tool that is simple,efficient, easy and necessary for asthma patients. Asthma Control Test (ACT)is a screening test In the form :if a questionnaire :in a clinical assessment of patients withasthma. Method : This study wa cross se·::tionalstudy,in 61 patients with asthma were taken by consecutive samplin£. The whole subject of study conduct ACT questionnaire and splrometry followed by examination. The analysis data using the ROC curve for diagnostic value and Pearson correlation test. Result :61 subjects,39 ternale and 22 male subjects with a mean age of 54.44 yea•s. Based on thevalue of the subject ACT consists of 31.1% is well controllec, partly controlled 21.3% and 47.5